PENGARUH KELEKATAN AMAN ORANG TUA TERHADAP REGULASI EMOSI SISWA KELAS VIII DI SMP NEGERI 11 KOTA JAMBI - Natalia Ayu Garini; K.A. Rahman; Muhammad Zulfikar (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
The role of parents in regulating and supporting adolescents’ emotions is very important because adolescence is a period of emotional vulnerability and significant personal development. Secure attachment is a warm, stable, and trusting emotional bond between parents and children, formed through consistent and responsive interactions from infancy through adolescence. This study aims to determine whether there is an influence of secure attachment to parents on the emotional regulation of eighth-grade students at SMP Negeri 11 Jambi City. The sample in this study consisted of 203 students from a popilation of 411, selected using simple random sampling. Analysis techniques were carried out with the help of SPSS V.27, including normality tests, linearity tests, simple regression tests, and hypothesis testing. The results showed that the secure attachment received by eighth-grade students at SMP Negeri 11 Jambi City is in the high category, with a percentage of 68,78%, while the emotional regulation of these students is also in the high category, with a percentage of 66,49%. The relationship between parental secure attachment and student emotional regulation is positive and significant, with a determination analysis result of  0,1225 or 12,25% which is categorizes as low but certain.